Cognitive regulation of ventromedial prefrontal activity evokes lasting change in the perceived self‐relevance of persuasive messaging. Issue 9 (17th February 2019) - Doré, Bruce P.; Cooper, N.; Scholz, C.; O'Donnell, Matthew B.; Falk, Emily B.
Abstract: Persuasive messages can change people's thoughts, feelings, and actions, but these effects depend on how people think about and appraise the meaning of these messages. Drawing from research on the cognitive control of emotion, we used neuroimaging to investigate neural mechanisms underlying cognitive regulation of the affective and persuasive impact of advertisements communicating the risks of binge drinking, a significant public health problem. Using cognitive control to up‐regulate (vs. down‐regulate) responses to the ads increased: negative affect related to consequences of excessive drinking, perceived ad effectiveness, and ratings of ad self‐relevance made after a one‐hour delay. Neurally, these effects of cognitive control were mediated by goal‐congruent modulation of ventromedial prefrontal cortex and distributed brain patterns associated with negative emotion and subjective valuation. These findings suggest that people can leverage cognitive control resources to deliberately shape responses to persuasive appeals, and identify mechanisms of emotional reactivity and integrative valuation that underlie this ability. Specifically, brain valuation pattern expression mediated the effect of cognitive goals on perceived message self‐relevance, suggesting a role for the brain's valuation system in shaping responses to persuasive appeals in a manner that persists over time.